ENVIRONMENTAL CIVIL LIABILITY AND THE AMAZON DEFORESTATION CRISIS: ANALYSIS OF THE LIMITS OF ECOLOGICAL DAMAGE REPARATION (REMUNOM, 2026)
This article examines the effectiveness of environmental civil liability in Brazil in addressing illegal deforestation in the Amazon, articulating normative foundations and theoretical reflection. It begins with the consolidation of the right to an ecologically balanced environment as a fundamental right in the 1988 Constitution, as well as the structure of environmental civil liability, characterized by strict liability, the full risk theory, and the principle of full reparation. A qualitative, exploratory, and descriptive methodology is adopted, based on bibliographic and documentary review, including the analysis of legislation, official data, and relevant judicial decisions. The study then analyzes recent data on Amazon deforestation, which reveal the persistence of high levels of environmental degradation despite a consistent legal and institutional framework. It also examines administrative and judicial enforcement mechanisms, highlighting the role of the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) and the Public Prosecutor’s Office, as well as obstacles such as difficulties in identifying offenders, low enforcement of sanctions, and procedural delays. The feasibility of environmental damage reparation is discussed, considering the irreversibility of certain impacts and technical limitations of ecological restoration. The article concludes that a gap remains between normative density and practical application.